2016
DOI: 10.1148/radiol.2016160209
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness Measurements with MR Elastography: Agreement and Repeatability across Imaging Systems, Field Strengths, and Pulse Sequences

Abstract: Purpose To prospectively assess agreement and repeatability of magnetic resonance (MR) elastography liver stiffness measurements across imager manufacturers, field strengths, and pulse sequences. Materials and Methods This prospective cross-sectional study was approved by the institutional review board; informed consent was obtained from all subjects. On the basis of an a priori power calculation, 24 volunteer adult subjects underwent MR elastography with four MR imaging systems (two vendors) and multiple puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 28 publications
0
96
0
Order By: Relevance
“…The high interexamination ICC (0.86) observed in our study for this technique is consistent with previously reported results (ICC ~ 0.85 – 0.94; [13,14,17,32]). The other MRE technical variants examined in this study have not been described as extensively in the literature[33]. Our study suggests that most of these variants – including 2D MRE using a flexible driver at end-inspiration, and 3D MRE under any tested condition – are likely to have good repeatability.…”
Section: Discussionmentioning
confidence: 79%
“…The high interexamination ICC (0.86) observed in our study for this technique is consistent with previously reported results (ICC ~ 0.85 – 0.94; [13,14,17,32]). The other MRE technical variants examined in this study have not been described as extensively in the literature[33]. Our study suggests that most of these variants – including 2D MRE using a flexible driver at end-inspiration, and 3D MRE under any tested condition – are likely to have good repeatability.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, as people tend to focus more on successful results rather than technical failure when presenting the results of studies, the failure rates of MRE have not been reported well. A limited number of studies have reported on the technical failure rate of MRE, and fewer studies have made comparisons regarding the failure rates between these two sequences. The results from the studies are also limited by their small sample sizes and the resulting low levels of evidence.…”
mentioning
confidence: 99%
“…Another limitation is that we kept the imaging matrix unchanged within a wide field of view range to maintain reasonable scan time in our pig model. However, this effect could have been counted in several repeatability and reproducibility studies (34-36). However, a systematic evaluation is still needed.…”
Section: Discussionmentioning
confidence: 99%